Two new species of Aphelandra (Acanthaceae) with a rugose corolla from central Peru - Villanueva-Espinoza, Rosa; Fernandez-Hilario, Robin; Pillaca-Huacre, Luis (Phytotaxa, 2020)
Two new species of Aphelandra, A. rugosa and A. apecoi, are described and illustrated from the Huánuco region of Peru. Aphelandra rugosa is related to A. mucronata and A. weberbaueri but differs from both species in having larger dark red calyx, subequal sepals, corolla upper lip with 4 lobes and stamens exceeding the tip of corolla. Aphelandra apecoi is related to A. zamorensis, but differs from the latter in having long-pedunculate spikes, larger calyx, and a corolla with unequal upper lip lobes.